Quality of Life and Associated Conditions in Women with Fibromyalgia Syndrome - Didem Sezgin Özcan; Meltem Aras; Belma Füsun Köseoğlu; Şeyma Şentürk Güven (Galenos Yayinevi, 2013)
Aim: Fibromyalgia syndrome (FMS) is a rheumatic disease of unknown etiology, characterized by widespread pain and tender points at specific anatomical regions. Patients' daily activities and quality of life (QOL) might be affected by severe pain which is accompanied by fatigue, sleep disturbance and psychiatric symptoms. In this study, the QOL of women with fibromyalgia and the relationship between the QOL and socio-demographic characteristics, depression and sleep disturbance were investigated. Material and Methods: One hundred women with diagnosis of FMS according to the ACR (American College of Rheumatology) criteria (1990) were included. Socio-demographic characteristics were questioned in detail. Fibromyalgia Impact Questionnaire (FIQ) was used to assess QOL. Visual Analogue Scale (VAS) (0-10cm) was used to assess the severity of widespread pain and sleep disturbance. Depression was assessed by using Beck Depression Inventory (BDI). Results: Mean age was 42.2±9.5 years and mean duration of disease was 32.3±29.4 months. The mean FIQ total score was 59.49±14.25 and %26 of the patients were severely affected. There was no association between FIQ scores and socio-demographic variables. There were statistically significant relationship between FIQ scores and pain VAS, sleep disturbance VAS and BDI scores. In the multivariate regression analysis, pain was the most contributing variable to FIQ level and it was followed by sleep disturbance and depression scores, respectively. Conclusion: Depression and sleep disturbances are commonly encountered in patients with fibromyalgia which result in deterioration of QOL. Given that the final purpose of the management of fibromyalgia is to improve the quality of life, clinical evaluation of depression and sleep disturbances should be regarded to guide therapy. (Turkish Journal of Osteoporosis 2013;19: 42-7)